2016
DOI: 10.2147/rmhp.s106068
|View full text |Cite
|
Sign up to set email alerts
|

The Lebanese–Syrian crisis: impact of influx of Syrian refugees to an already weak state

Abstract: BackgroundLebanon, a small Middle Eastern country facing constant political and national unity challenges with a population of approximately 300,000 Palestinian and Iraqi refugees, has welcomed more than 1.2 million Office of the United Nations Commissioner for Refugees (UNHCR)-registered Syrian refugees since 2012. The Government of Lebanon considers individuals who crossed Lebanese–Syrian borders since 2011 as “displaced”, emphasizing its long-standing position that Lebanon is not a state for refugees, refus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 7 publications
0
23
1
Order By: Relevance
“…In our present study, we obtained an alarming number going up to a prevalence of 47.1% broadly consistent with the findings of the international survey of sleeping problems in the United States, Europe, and Japan and this survey revealed a prevalence of sleeping problems of 56% in the United States, 31% in Western Europe, and 23% in Japan [25], whereas our study showed a much higher rate compared to a study done in the Family Medicine Outpatient Department at St. Philomena's Hospital, Bengaluru, where 33% of the adult population sampled had chronic insomnia [26]. This high prevalence might be due to the fact that Lebanon had witnessed a series of wars, local armed combats, and terrorist attacks [27], in addition to a series of crises including clean water penury, electrical power, and waste management had overwhelmed the country [27]. Moreover, a high number of Syrian refugees had led to high levels of unemployment and competition for employment with locals.…”
Section: Prevalence Of Insomniacontrasting
confidence: 79%
“…In our present study, we obtained an alarming number going up to a prevalence of 47.1% broadly consistent with the findings of the international survey of sleeping problems in the United States, Europe, and Japan and this survey revealed a prevalence of sleeping problems of 56% in the United States, 31% in Western Europe, and 23% in Japan [25], whereas our study showed a much higher rate compared to a study done in the Family Medicine Outpatient Department at St. Philomena's Hospital, Bengaluru, where 33% of the adult population sampled had chronic insomnia [26]. This high prevalence might be due to the fact that Lebanon had witnessed a series of wars, local armed combats, and terrorist attacks [27], in addition to a series of crises including clean water penury, electrical power, and waste management had overwhelmed the country [27]. Moreover, a high number of Syrian refugees had led to high levels of unemployment and competition for employment with locals.…”
Section: Prevalence Of Insomniacontrasting
confidence: 79%
“…As of April 2018, slightly less than a million Syrian individuals were registered with the UNHCR in Lebanon as refugees, of which, 36% (354,326 individuals) reside in the Bekaa, a rural and underdeveloped region that is geographically close to the Syrian–Lebanese border [ 33 ]. The high influx of Syrian refugees to the impoverished host communities in the Bekaa have added further strain to the limited resources and basic services available, including access to adequate food, water, shelter, education, and health services [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This growth is continuing despite some borders surrounding Syria being closed and in part due to a rising birth rate in refugee camps [ 5 , 6 ]. This creates acute challenges for neighboring/receiving countries in terms of ensuring adequate capacity to offer essential services such as food, water, housing, security, and specifically healthcare [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%